2019
DOI: 10.1007/s10803-019-03969-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Communication Differences in Autism Spectrum Disorder and First-Degree Relatives: A Study of Looking and Speaking

Abstract: This study examined narrative ability in ASD and parents across two contexts differing in structure and emotional content, and explored gaze patterns that may underlie narrative differences by presenting narrative tasks on an eye tracker. Participants included 37 individuals with ASD and 38 controls, 151 parents of individuals with ASD and 63 parent controls. The ASD and ASD parent groups demonstrated lower narrative quality than controls in the less structured narrative task only. Subtler, context-dependent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 58 publications
4
38
0
1
Order By: Relevance
“…Our results indicate that not every pictorial stimulus may be equally good in order to differentiate the speech of people with ASD from the speech of peers with TD, particularly using natural language processing techniques. Prior evidence suggests that narrative context matters: participants with ASD exhibited more difficulties in less structured tasks, i.e., narratives of personal experiences or pictures from the Thematic Apperception Test [43,44]. On the contrary, Baixauli et al [6] reported no significant differences for the type of narrative used in several studies analyzed in their meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that not every pictorial stimulus may be equally good in order to differentiate the speech of people with ASD from the speech of peers with TD, particularly using natural language processing techniques. Prior evidence suggests that narrative context matters: participants with ASD exhibited more difficulties in less structured tasks, i.e., narratives of personal experiences or pictures from the Thematic Apperception Test [43,44]. On the contrary, Baixauli et al [6] reported no significant differences for the type of narrative used in several studies analyzed in their meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties include difficulties with reciprocity (i.e., building on a conversational partner's statement), overly formal language, off topic remarks, introduction of topics without providing adequate background information, and difficulties with suprasegmental features of speech such as reduced variation of intonation (de Villiers et al 2007;Paul 2012, 2013;Diehl et al 2009;Lam and Yeung 2012;Klusek et al 2014). Prior work suggests that individuals with ASD also demonstrate difficulties with narration (i.e., storytelling), with particular difficulty imbuing narratives with a psychological perspective to explain protagonists' actions and motivations (Colle et al 2008;Lee et al 2017Lee et al , 2019Losh and Capps 2003;Losh and Gordon 2014;Loveland et al 1990;Loveland and Tunali 1993;Tager-Flusberg and Sullivan 1995). Further, individuals with ASD appear to exhibit the greatest difficulty in communicative contexts that are lessstructured, emotionally evocative, and openended, with relative strengths in highly structured contexts such as wordless picture books (Losh and Capps 2003;Lee et al 2019).…”
Section: Current Knowledgementioning
confidence: 99%
“…Prior work suggests that individuals with ASD also demonstrate difficulties with narration (i.e., storytelling), with particular difficulty imbuing narratives with a psychological perspective to explain protagonists' actions and motivations (Colle et al 2008;Lee et al 2017Lee et al , 2019Losh and Capps 2003;Losh and Gordon 2014;Loveland et al 1990;Loveland and Tunali 1993;Tager-Flusberg and Sullivan 1995). Further, individuals with ASD appear to exhibit the greatest difficulty in communicative contexts that are lessstructured, emotionally evocative, and openended, with relative strengths in highly structured contexts such as wordless picture books (Losh and Capps 2003;Lee et al 2019).…”
Section: Current Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that individuals with ASD tend to look less at the eyes when exploring faces and more at the mouth ( Klin et al, 2002 ), spend less time looking at social features in scenes ( Lee et al, 2019 ) and demonstrate decrease gaze-language coordination ( Nayar et al, 2018 ) compared to controls. In parents of individuals with ASD, Lee et al (2019) additionally demonstrated that parents of individuals with ASD who met criteria for the BAP showed distinct gaze profiles when viewing emotionally evocative scenes depicted in the thematic apperception test (TAT), allotting greater attention to faces in scenes in which the faces were featured most prominently, and more attention toward the setting in more complex images with salient setting features. These differences in viewing patterns were associated with the quality of participants’ narratives when telling stories about these scenes (particularly in the group which met criteria for the BAP), suggesting that atypical attentional patterns importantly relate to social communication.…”
Section: Introductionmentioning
confidence: 99%